2010
DOI: 10.6026/97320630004336
|View full text |Cite
|
Sign up to set email alerts
|

An integrated database for the enhanced identification of silkworm gene resources

Abstract: The National Academy of Agricultural Science (NAAS) has developed a web-based database to provide characterization information in silkworm. The silkworm database has four major function menus: variety searching, characterization viewing, general information and photo gallery. It provides 321 silkworm varieties characterization information for six different regions namely, Korean, Japanese, Chinese, European, Tropical and non­classified group. Additionally, the database provides 1,132 photo images regarding lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Variety searching, characterization viewing, general information, and a photo gallery are the four main function menus in the silkworm database. The database provides of 321 silkworm gene resources and 1,132 images regarding life cycle of various silkworm varieties" [23]. With the help of the National Bioresource Project, which began in 2002, resources for mutants of B. mori have been concentrated at Kyushu University in Japan.…”
Section: Genetic Resource Databasesmentioning
confidence: 99%
“…Variety searching, characterization viewing, general information, and a photo gallery are the four main function menus in the silkworm database. The database provides of 321 silkworm gene resources and 1,132 images regarding life cycle of various silkworm varieties" [23]. With the help of the National Bioresource Project, which began in 2002, resources for mutants of B. mori have been concentrated at Kyushu University in Japan.…”
Section: Genetic Resource Databasesmentioning
confidence: 99%
“…of 321 varieties collected from different regions including Korea, China, Japan, Europe, tropical region and non-classified group along with 1132 photo images of different life stages of these silkworm varieties. It also allows the users to access information regarding silkworm races such as univoltine, bivoltine, multivoltine and others ( 53 ). SilkwormBase hosts around 456 phenotypically classified strains and a total of 419 genes.…”
Section: Silkworm Databasesmentioning
confidence: 99%
“…With the progress of genomic technology, access to information about silkworms such as genome sequencing and genetic markers has accelerated (Kim et al 2010). Various genotypes have shown that there are many differences in quantitative and qualitative traits which have an important part in silkworm efficiency (Nagaraju & Singh 1997).…”
Section: Expected Breeding Valuementioning
confidence: 99%